Categories and Dispositions. A New Look at the Distinction between Primary and Secondary Properties - Roberta Lanfredini (Philosophies, 2018)
The distinction between primary and secondary properties establishes the absolute priority, both ontological and epistemological, of quantity (objective and measurable) over quality (subjective and ineffable). In between the two properties, primary and secondary, are the dispositional properties, for example fragility, malleability, rigidity, and so on. But, from an ontological point of view, what are dispositional properties? This contribution takes into consideration two possible answers to this question: the one according to which the dispositional properties are invariant in variation and another according to which they are powers. The second answer is in turn subject to two different interpretations. We can consider dispositions, or powers, as integrally reducible to behavioral events (solubility, for example, is reduced to the fact that a certain substance melts when immersed in a certain liquid), or physical (the fragility of glass, for example, is reduced to the physical structure underlying it). However, we can consider powers as ontologically autonomous and not-grounded. This contribution aims to investigate the latter solution, with particular reference to the apparently oxymoronic notion of physical intentionality. This notion will provide a new, dynamic, and evolutionary version of the concept of disposition and at the same time offer a new look at the distinction between primary and secondary properties.